Toxicosis with grapes or raisins causing acute kidney injury and neurological signs in dogs. (7th September 2020) - Schweighauser, Ariane; Henke, Diana; Oevermann, Anna; Gurtner, Corinne; Francey, Thierry
Abstract: Background: The ingestion of grapes or raisins has been reported to cause acute kidney injury (AKI) in dogs, with a clinical picture dominated by early gastrointestinal signs and rapidly developing uremia. Ataxia is mentioned in a few reports, but not further characterized. Objectives: To evaluate the clinical, laboratory, and pathological features of dogs diagnosed with grape or raisin toxicosis (GRT) with emphasis on renal and neurological manifestations, compared to a control group of dogs with AKI from other causes. Animals: Fifteen client‐owned dogs with GRT and 74 control dogs. Methods: Retrospective study over 17 months. Results: All dogs with GRT were presented with severe AKI (grade 4, n = 5; grade 5, n = 10). Eleven dogs (73%) had marked forebrain, cerebellar, or vestibular signs. These manifestations dominated the clinical picture in some dogs, but were not associated with the severity of azotemia or the presence of systemic hypertension. Eight dogs (53%) survived, and 5 dogs experienced a complete neurological recovery. Causes of death were unrelated to the neurological manifestations. Neuropathological examination of 4 dogs did not identify any structural central nervous system abnormality. Only 2 control dogs (3%) displayed neurological signs with seizures unrelated to the AKI; 42 control dogs (57%) survived. Conclusions and Clinical Importance: Severe forebrain, cerebellar, or vestibular signs may be an important feature of GRT and dominate the early clinical picture. The described features suggest a reversible functional brain injury specific to GRT and unrelated to uremia.